Does high e-government adoption assure stronger security? A cross-country analysis of Australia and Thailand. - Thompson, Nik; Mullins, Antony; Chongsutakawewong, Thanavit (Elsevier, 2019)
We present the first comprehensive audit and comparison of e-government website security in two countries. Australia was selected for its high level of e-government adoption, while Thailand was selected in contrast as a developing nation. Through our audit of 800 pages across 40 websites, we reveal numerous security vulnerabilities suggesting that the high adopters of e-government may not always be providing better protection to their citizens. Alarmingly, the most basic web security measure, the use of Hypertext Transfer Protocol Secure encryption was only used in half of Australian and one-third of Thai sites. Our methodology included content analysis of policies and encryption, followed by security vulnerability testing, to provide the first baseline data on these two countries. Statistical analysis suggests that far from being the benchmark for security, Australian e-government sites do not significantly differ from Thai sites in their vulnerability level. The implications of these findings are examined, and recommendations are made for practice. It is hoped that these insights into the current state of security provide a needed stimulus to focus more on the practical information security aspects of e-government.